Testing the moderating effect of the perceived importance of the coach on the relationship between perceived coaching feedback and athletes` perceptions of competence - Amorose, A. J.; Nolan-Sellers, W. (International Journal of Sports Science & Coaching, 2016)
The purpose of this study was to explore whether the importance athletes place on behaviors of their coach moderates the relationship between athletes` perceptions of their coach`s feedback and their own perceptions of competence. Adult female softball players participating in a competitive league completed questionnaires assessing (a) their perceptions of competence, (b) their perceptions of feedback they typically receive from their coach, and (c) the importance they place on what their coach says and does. Overall, results of various regression analyses provided general support for the hypothesis that a stronger effect of coach feedback on athletes` perceptions of competence would emerge for those athletes placing greater importance on their coach. This effect was primarily a function of variations in the interpretation of positive and informational feedback. Results are discussed relative to theory and research on coaching behavior and self-perceptions. ABSTRACT FROM AUTHOR